Geographical diversification strategy in a small open economy. - Sng, Yih. (2008)
This report will test two main hypotheses - that international diversification is a positively related to firm performance, and that international diversification reduces the impact of regional economic crisis on firm performance. This is done by exploring the geographic diversification strategies of Singapore firms and the correlation with performance in two time periods.